👤

Daca x € R* și x + 1 pe x = 3 , calculați x la 2 + 1 pe x la 2 și x la 4 + 1 pe x la 4

Răspuns :

[tex]x+ \frac{1}{x}=3 \\ \\ (x+ \frac{1}{x})^2=3^2 \\ \\ x^2 + 2 \cdot x \cdot \frac{1}{x}+ \frac{1}{x^2} = 9 \\ \\ x^2+ 2+\frac{1}{x^2} =9 \\ \\ \boxed{x^2+ \frac{1}{x^2}=7 } [/tex]

[tex](x^2+ \frac{1}{x^2} )^2=7^2 \\ \\ x^4+2 \cdot x^2 \cdot \frac{1}{x^2}+ \frac{1}{x^4}=49 \\ \\ x^4+2+ \frac{1}{x^4}=49 \\ \\ \boxed{x^4+ \frac{1}{x^4}=47 } [/tex]
[tex]x+ \frac{1}{x} =3[/tex]⇒[tex]( x+ \frac{1}{x}) ^{2} =9[/tex]
[tex] x^{2} +2*x* \frac{1}{x}+ \frac{1}{ x^{2} } =9 [/tex]
[tex] x^{2} +2+ \frac{1}{ x^{2} } =9[/tex]
[tex] x^{2} + \frac{1}{ x^{2} } =9-2 [/tex]
[tex] x^{2} + \frac{1}{ x^{2} } =7[/tex]
daca [tex] x^{2} + \frac{1}{ x^{2} } =7[/tex]
atunci [tex] (x^{2} + \frac{1}{ x^{2} } )^{2} = 7^{2} [/tex]
         [tex] x^{4} +2* x^{2} * \frac{1}{ x^{2} } + \frac{1}{ x^{4} } =49[/tex]
         [tex] x^{4} +2+ \frac{1}{ x^{4} } =49[/tex]
         [tex] x^{4} + \frac{1}{ x^{4} } =49-2[/tex]
         [tex] x^{4} + \frac{1}{ x^{4} } =47[/tex]